Case Report: Exome and RNA Sequencing Identify a Novel de novo Missense Variant in HNRNPK in a Chinese Patient With Au-Kline Syndrome - Pan, Xin; Liu, Sihan; Liu, Li; Zhang, Xu; Yao, Hong; Tan, Bo (Frontiers in Genetics, 2022)
Au-Kline syndrome is a severe multisystemic syndrome characterized by several congenital defects, including intellectual disability. Loss-of-function and missense variants in the HNRNPK gene are associated with a range of dysmorphic features. This report describes an eleven-year-old Chinese boy with intellectual disability and developmental delays. Family-based whole-exome and Sanger sequencing identified a de novo missense variant in HNRNPK (NM_002140.3: c.143T>A, p. Leu48Val). In silico analysis predicted that this variant would be damaged in a highly conserved residue in the K homology 1 (KH1) domain. Bioinformatic analysis showed that the affinity change (ΔΔG) caused by this variant was -0.033 kcal/mol, indicating that it would have reduced affinity for RNA binding. Transcript analysis of the peripheral blood from this case found 42 aberrantly expressed and 86 aberrantly spliced genes (p-value <0.01). Functional enrichment analysis confirmed that the biological functions of these genes, including protein binding and transcriptional regulation, are associated with HNRNPK. In summary, this study identifies the first Chinese patient with a novel de novo heterozygous HNRNPK gene variant that contributes to Au-Kline syndrome and expands current knowledge of the clinical spectrum of HNRNPK variants.